Governing uranium in the United Kingdom - Molly Berkemeier; Wyn Q. Bowen; Christopher Hobbs; Matthew Moran (Danish Institute for International Studies (DIIS), 2014)
This country report is the first study of uranium governance in the United Kingdom. It explores the UK's approach to regulating natural uranium and provides a historical overview of uranium procurement and usage. The report documents British and Euratom nuclear legislation, regulation and implementation, including export/import and transportation regulations. This case study is part of the large 'Governing Uranium' project on uranium governance, led by DIIS, the Danish Institute for International Studies. The project identifies governance gaps in uranium accountability and control and provide policy recommendations for improving front-end transparency, security, and regulation.
Keywords: 300